The entity of economic dynamics - Filiakova, T. (ХНУ ім. В. Н. Каразіна, 2012)
The importance to solve the problem of the entity of economic dynamics with the help of spatial-temporal dynamics analysis in modern life is substantiated. Various methods and approaches for carrying out analysis of spatial-temporal dynamics in the system of economic dynamics are considered. The basis of the generalized analysis of spatial-temporal dynamics in economic system is offered.
Определена важность решения проблемы сущности экономической динамики при помощи пространственно-временного динамического анализа в современном мире. Рассмотрены различные методы и подходы для ведения анализа пространственно-временной динамики в системе экономической динамики. Представлен базовый анализ пространственно-временной динамики в экономической системе.
Keywords: movement; volatility; growth; value; economic dynamics